2019
DOI: 10.18203/2349-2902.isj20191485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraincisional vs intraperitoneal bupivacaine for the control of postoperative pain after laparoscopic cholecystectomy

Abstract: The main reason for using multimodal analgesia techniques is to avoid possible side effects by limiting the utilisation of commonly used opioids to provide postoperative analgesia. 9 So far many studies have been done using intraperitoneal or intraincisional local anaesthetic infiltration, but the results have been conflicting. [10][11][12][13][14] The aim of our study was to compare the ABSTRACT Background: The aim of this study was to compare the efficacy of infiltration of local anaesthetic bupivacaine at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
0
1
Order By: Relevance
“…Subarachnoid morphine affects both superficial and deep visceral postoperative pain, whereas the TAP block affects only the superficial incisional pain, and this can explain the superiority of subarachnoid morphine in comparison with TAP block for post cesarean pain management. In disagreement with our study, the study done by Bacha UQ, et al [22] They found that intra-incisional infiltration of bupivacaine is more effective than IP infiltration for postoperative pain relief. It is easier to apply and there is less requirement of postoperative analgesics.…”
Section: Discussioncontrasting
confidence: 99%
“…Subarachnoid morphine affects both superficial and deep visceral postoperative pain, whereas the TAP block affects only the superficial incisional pain, and this can explain the superiority of subarachnoid morphine in comparison with TAP block for post cesarean pain management. In disagreement with our study, the study done by Bacha UQ, et al [22] They found that intra-incisional infiltration of bupivacaine is more effective than IP infiltration for postoperative pain relief. It is easier to apply and there is less requirement of postoperative analgesics.…”
Section: Discussioncontrasting
confidence: 99%